Mutual information analysis reveals bigeminy patterns in Andersen–Tawil syndrome and in subjects with a history of sudden cardiac death - Núñez-Acosta, Elisa; Lerma, Claudia; Márquez, Manlio F.; José, Marco V. (Physica A, 2012)
Herein we introduce the Mutual Information Function (MIF) as a mathematical method to analyze ventricular bigeminy in certain pathological conditions of the heart known to be associated with frequent ventricular arrhythmias. In particular, we show that the MIF is sensitive enough to detect the bigeminy pattern in symbolic series from patients with Andersen–Tawil syndrome as well as in a group of patients from the Sudden Cardiac Death Holter Databases. The results confirm that MIF is an adequate method to detect the autocorrelation between the appearance of sinus and ventricular premature beats resulting in a bigeminy pattern. It is also shown that MIF reflects the bigeminy patterns as a function of the percentage of ventricular premature beats present in the symbolic series and also as a function of the percentage of bigeminy. The MIF was also useful to establish a consistent difference in the bigeminy pattern related to the diurnal and nocturnal periods presumably associated to the circadian rhythm of the heart. Understanding of the ventricular bigeminy patterns throughout 24-hours could provide some insights into the pathogenesis of ventricular tachyarrhythmias in these pathological conditions.